An Evaluation to Assess the Knowledge regarding Palliative Care in Neonatal Nursing among Staff Nurses Working in Selected Hospitals at Bangalore - Jemy Joseph (International Journal of Public Health Science (IJPHS), 2013)
The neonatal unit frequently occupied by newborns that are marginally viable or critically unwell and could be considered as terminally ill. It is a busy, highly technical environment with advanced life saving medical equipments, at its disposal. The technology has had a profound effect on neonatal nursing practice. The escalation of technology and medical advances has been followed by an increase in later disabilities. Many devices have altered from being one of the supporting clinical practices to that of being an essential requirement in treatment delivery. Even after the use of all settings.  Some newborns will die in the NICU. The mortality and morbidity rate is still high. This has given rise to many ethical issues including withdrawal of intensive care therapies. The conceptual framework for the study is based on Health Belief Model. Health Beliefs are person’s knowledge, ideas and attitude, about health and illness. In this study various literature was reviewed which includes, the research design selected for the study was Descriptive research design. The dependent variable and independent variable were selected for the research.DOI: http://dx.doi.org/10.11591/ijphs.v2i2.2779